Total atheism: secular activism and the politics of difference in South India - Binder, Stefan (Methodology and history in anthropology, 2020)
"Exploring lived atheism in the South Indian states of Andhra Pradesh and Telangana, this book offers a unique insight into India's rapidly transforming multi-religious society. It explores the social, cultural, and aesthetic challenges faced by a movement of secular activists in their endeavors to establish atheism as a practical and comprehensive way of life. On the basis of original ethnographic material and engaged conceptual analysis, Total Atheism develops an alternative to Eurocentric accounts of secularity and critically revisits central themes of South Asian scholarship from the hitherto marginalized vantage point of radically secular and explicitly irreligious atheists in India"--